Operations Management 2013
DOI: 10.5772/55065
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Human Reliability Analysis Techniques in Manufacturing Operations

Abstract: In recent years, there has been a decrease in accidents due to technical failures through technological developments of redundancy and protection, which have made systems more reliable. However, it is not possible to talk about system reliability without addressing the failure rate of all its components; among these components, "man" – because his rate of error changes the rate of failure of components with which he interacts. It is clear that the contribution of the human factor in the dynamics of accidents –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In human reliability analysis models, the probability of human error is calculated based on the activities of the worker and the factors that shape performance. Factors that shape performance are related to the work environment or mental and physical capabilities of the workforce or both 15 . Human reliability analysis models are divided into two main categories: quantitative models and qualitative models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In human reliability analysis models, the probability of human error is calculated based on the activities of the worker and the factors that shape performance. Factors that shape performance are related to the work environment or mental and physical capabilities of the workforce or both 15 . Human reliability analysis models are divided into two main categories: quantitative models and qualitative models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, many researchers realize that cognitive activities are supposed to be considered. In the first‐generation methods, the effects of cognition may be incorporated in the HEP assigned to the human error of a specific task type, but they still lack cognition influence on human behaviors 14,35 . Specifically, Hollnagel indicated that the dichotomy classification of human behaviors, like success and failure, or error of commission and error of omission, makes it hard to perform a more detailed classification.…”
Section: Development Trends Of Hra In Nppsmentioning
confidence: 99%
“…Machines are directly affected by the environment or personnel during operation, 20 which may lead to independent or common‐cause failures of components, 21–24 thus directly affecting the reliability of the system. Meanwhile, human as one of the critical factors affecting system reliability, 25 the environment and machine will affect the HEP by influencing the performance shaping factors of the personnel. With the advancement of research, the study of system reliability has evolved from discussing the effects of machines and the environment to a comprehensive examination of the human‐machine‐environment interaction 26–28 .…”
Section: Introductionmentioning
confidence: 99%
“…HE is one of the most significant contributors to the reliability of the system in MMSs. 60%−90% of MMS accidents are related to HEs, 25 which may result from performing tasks out of sequence, operating at the wrong time, applying the wrong force or direction, etc. Many studies have assessed the human reliability in the reliability assessment of MMS 26–28 .…”
Section: Introductionmentioning
confidence: 99%